(untitled) (Communications in Computational Physics, 2019)
In this work, the operator marching methods based on the modified Neumann-to-Dirichlet (NtD) map are developed to calculate the scattered fields from the periodic structures, especially diffraction gratings with metallic material. For the grating structures coated with the metallic material, the modified NtD map operator marching scheme is numerically stable for calculating the electromagnetic scattered fields. The modified NtD map operators are constructed by the integral equation (IE) method in each homogeneous medium of the layered medium structures, and avoid the blow up of the condition numbers from the challenging metallic material with the complex refractive index. For the calculations of the scattered fields from the diffraction grating structures, the modified NtD map operator marching method takes advantage of the periodic structure features, and avoids the calculations of the complicated quasi-periodic Green's function. Numerical results demonstrate that the proposed method achieves high accuracy and low computational workload for the scattered fields from both the dielectric and metallic diffraction grating structures.